Asebogenin suppresses thrombus formation via inhibition of Syk phosphorylation. (19th October 2022) - Li, Li; Xu, Xulin; Lv, Keyu; Zheng, Guijuan; Wang, Hao; Chen, Shuai; Huang, Lang; Liu, Yi; Zhang, Yadong; Tang, Zhaoming; Zhang, Lili; Wang, Jinyu; et al.
Abstract: Background and Purpose: Thrombosis is a major cause of morbidity and mortality worldwide. Platelet activation by exposed collagen through glycoprotein VI (GPVI) and formation of neutrophil extracellular traps (NETs) are critical pathogenic factors for arterial and venous thrombosis. Both events are regulated by spleen tyrosine kinase (Syk)‐mediated signalling events. Asebogenin is a dihydrochalcone whose pharmacological effects remain largely unknown. This study aims to investigate the antithrombotic effects of asebogenin and the underlying molecular mechanisms. Experimental Approach: Platelet aggregation was assessed using an aggregometer. Platelet P‐selectin exposure, integrin activation and calcium mobilization were determined by flow cytometry. NETs formation was assessed by SYTOX Green staining and immunohistochemistry. Quantitative phosphoproteomics, microscale thermophoresis, in vitro kinase assay and molecular docking combined with dynamics simulation were performed to characterize the targets of asebogenin. The in vivo effects of asebogenin on arterial thrombosis were investigated using FeCl3 ‐induced and laser‐induced injury models, whereas those of venous thrombosis were induced by stenosis of the inferior vena cava. Key Results: Asebogenin inhibited a series of GPVI‐induced platelet responses and suppressed NETs formation induced by proinflammatory stimuli. Mechanistically, asebogenin directly interfered with the phosphorylation of Syk at Tyr525/526, which is important for its activation. Further, asebogenin suppressed arterial thrombosis demonstrated by decreased platelet accumulation and fibrin generation and attenuated venous thrombosis determined by reduced neutrophil accumulation and NETs formation, without increasing bleeding risk. Conclusion and Implications: Asebogenin exhibits potent antithrombotic effects by targeting Syk and is a potential lead compound for the development of efficient and safe antithrombotic agents. Abstract :